2012
DOI: 10.3758/s13414-012-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical distance effects in visual search

Abstract: We present three experiments in which observers searched for a target digit among distractor digits in displays in which the mean numerical target-distractor distance was varied. Search speed and accuracy increased with numerical distance in both target-present and target-absent trials (Exp. 1A). In Experiment 1B, the target 5 was replaced with the letter S. The results suggest that the findings of Experiment 1A do not simply reflect the fact that digits that were numerically closer to the target coincidentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…From the perspective of numerical cognition, our results add to the list of findings that numerical magnitude not only affects purely cognitive judgments about the abstract order relations of numbers but extends to more versatile tasks in which motor efference copies are compared to sensory feedback. Our findings thus complement and extend earlier studies demonstrating that symbolic numerical magnitude systematically influences complex activities such as visual search (Schwarz & Eiselt, 2012;Sobel, Puri, & Faulkenberry, 2016), the scaling of manual force in motor commands (Fischer & Miller, 2008;Lindemann et al, 2007;, or the evaluation of the temporal order of events (Gevers et al, 2003;Müller & Schwarz, 2008;Schwarz & Eiselt, 2009). In contrast to these findings the present study is the first to report the a priori seemingly implausible finding shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…From the perspective of numerical cognition, our results add to the list of findings that numerical magnitude not only affects purely cognitive judgments about the abstract order relations of numbers but extends to more versatile tasks in which motor efference copies are compared to sensory feedback. Our findings thus complement and extend earlier studies demonstrating that symbolic numerical magnitude systematically influences complex activities such as visual search (Schwarz & Eiselt, 2012;Sobel, Puri, & Faulkenberry, 2016), the scaling of manual force in motor commands (Fischer & Miller, 2008;Lindemann et al, 2007;, or the evaluation of the temporal order of events (Gevers et al, 2003;Müller & Schwarz, 2008;Schwarz & Eiselt, 2009). In contrast to these findings the present study is the first to report the a priori seemingly implausible finding shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Schwarz and Eiselt ( 2012 ) recently demonstrated that the magnitude information of different simultaneously presented Arabic digits becomes automatically activated and affects the visual search for a target number in these displays. The authors required their participants to find a target digit among distractor digits in displays in which the average numerical distance between the target and distractors was systematically varied.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical meaning is extracted quickly from visual displays (Corbett, Oriet, & Rensink, 2006). Indeed, Schwarz and Eiselt (2012) found that the presence of numerically similar distractors (e.g., 4, 6) decreased speed and accuracy in search for the number 5 compared with dissimilar distractors (e.g., 1, 9), suggesting that attention was drawn to digits that were numerically close to the target value. They did not find this pattern of results when participants searched for the letter S, even though it is highly visually similar to the digit 5, suggesting that the visual characteristics of the numbers were unlikely to be driving their semantic effects.…”
Section: Documented Examples Of Usagementioning
confidence: 99%
“…Godwin, Hout, and Menneer (2014) built upon the study by Schwarz and Eiselt (2012) by quantifying visual similarity using MDS ratings of the digits, and by tracking the oculomotor behavior of our participants. One group of participants provided visual similarity ratings for the numbers 0–9; we then analyzed the data using MDS, and indexed visual similarity via the distance between each pair of numbers in MDS space.…”
Section: Documented Examples Of Usagementioning
confidence: 99%
See 1 more Smart Citation